SISTEM PENDUKUNG KEPUTUSAN PENILAIAN TANAMAN ANGGREK PADA UD. SANJIWANI ORCHID MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING - Erni Dianassari; Taufiq Baidawi (Swabumi, 2015)
Orchids is one of the ornamental plants that attract many people. In deciding good quality of orchids need to considerseveral specific criteria, that is : the age of plants, the height of plants, condition of the leafs, amount of the stalks, andamount of the flowers . Quality assessment system of orchids that still using the manual method is not very effective. Tohelp to determine the assessment of orchids that have superior quality it needed a decision support system. Therefore, itis necessary to build Decision Support System Of Orchid’s Assessment. This system uses the Simple Additive weightingmethod (SAW) which has the ability to solve the problem of multiple criteria, so it can generate the sequence prioritiesselection of superior quality of orchids according to predefined criteria. From the test results, it is concluded that theDecision Support System Of Orchid’s Assessment has been successfully developed and display ranking of the results ofthe assessment of orchids.